Study of the Romanian sugar beet market in the period 2010-2016 - Alexandra-Marina Brǎtulescu; Diana Creţu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
Sugar beet is of particular importance in the root market, being a biennial plant grown for sugar production, also used in natural medicine, cultivated for its fleshy root used as a vegetable in the human diet and as a fodder plant. This paper analyzes the data on the evolution of sugar beet areas and production in Romania, as well as the sales price of sugar beet. Another aspect considered in this paper is the one related to the consumption of sugar beet in the period 2010-2016.
Keywords: Q13; J11; 330; sugar beet; food; prices; agri-food market